2022
DOI: 10.1002/ldr.4209
|View full text |Cite
|
Sign up to set email alerts
|

Restoring subsided coal mined land to farmland using optimized placement of Yellow River sediment to amend soil

Abstract: Underground coal mining causes land subsidence and large areas of cultivated land are destroyed. The Yellow River interlayer filling reclamation technology is a powerful way to restore cultivated land. Understanding the mechanism of action of interlayers in reconstructed soil filled with Yellow River sediment is essential to achieving sustainable land management in the Yellow River regions. Column experiments and field experiments were conducted to explore optimum interlayer placement in reconstructed soil wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, in terms of physical and mechanical properties, the Yellow River sediment has an inhomogeneity coefficient of 1.75 and a curvature coefficient of 1.36, with more uniform particle sizes and poorer gradation, which is intuitively reflected by the fact that the reclaimed farmland is prone to the leakage of water and fertilizer compared with the control farmland. Zhenqi Hu [26] proposed the principle and method of sandwich-type soil reconstruction, and through the study of multiple profiles, Xiaotong Wang [27] found that the Yellow River sediment sandwich reclamation reduces seepage.…”
Section: Causes Of Productivity Barriers and Soil Reconstruction In Y...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in terms of physical and mechanical properties, the Yellow River sediment has an inhomogeneity coefficient of 1.75 and a curvature coefficient of 1.36, with more uniform particle sizes and poorer gradation, which is intuitively reflected by the fact that the reclaimed farmland is prone to the leakage of water and fertilizer compared with the control farmland. Zhenqi Hu [26] proposed the principle and method of sandwich-type soil reconstruction, and through the study of multiple profiles, Xiaotong Wang [27] found that the Yellow River sediment sandwich reclamation reduces seepage.…”
Section: Causes Of Productivity Barriers and Soil Reconstruction In Y...mentioning
confidence: 99%
“…To address this, Zhenqi Hu [26] proposed a "sandwich-structure" method for the filling reclamation of soil using Yellow River sediment. Further research on multiple profiles have shown that this approach can effectively reduce water seepage when used for reclamation [27]. The sandwich design better retains water by enclosing sediment layers between more conducive materials.…”
Section: Introductionmentioning
confidence: 99%
“…The publications of the top five countries accounted for 28.26%, 10.82%, 9.63%, 6.07%, and 3.52%, respectively, indicating those countries made the greatest contributions to the research on LRER. For example, in China, there are many studies on LRER in coal mining areas, and the research areas are mainly concentrated in ecologically fragile areas in Northwest China [4,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and high water level areas in Eastern China [6,[45][46][47][48][49][50][51][52]. The research focuses include reclamation of open-pit coal mines [8,38,39,[53][54][55][56][57][58], reclamation of coal mining subsidence sites [7,51,[59][60][61][62][63][64]…”
Section: Main Countries/regions Conducting Research On Lrermentioning
confidence: 99%
“…Sandy interlayer structures are common in the field soil profile because of external forces, such as wind and sand, hydrology, and geology (Xue et al, 2020). In layered soil, the movement of moisture is closely related to the nature, thickness, texture, soil-layer order and groundwater table depth of the soil layer (Pillai et al, 2009;Shokri et al, 2010;Li et al, 2014;Hu et al, 2022;Wu et al, 2022). At the interface of different soil layers, the hydraulic characteristics of soil are discontinuous, which leads to the difference of hydraulic characteristics between homogeneous soil and heterogeneous soil.…”
Section: Introductionmentioning
confidence: 99%